2004
DOI: 10.1002/jnr.20387
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein reduces central nervous system inflammation, neurodegeneration, and cell death following kainic acid‐induced epileptic seizures

Abstract: We examined metallothionein (MT)-induced neuroprotection during kainic acid (KA)-induced excitotoxicity by studying transgenic mice with MT-I overexpression (TgMT mice). KA induces epileptic seizures and hippocampal excitotoxicity, followed by inflammation and delayed brain damage. We show for the first time that even though TgMT mice were more susceptible to KA, the cerebral MT-I overexpression decreases the hippocampal inflammation and delayed neuronal degeneration and cell death as measured 3 days after KA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 57 publications
8
112
0
Order By: Relevance
“…The underlying mechanisms of this inhibitory effect of ghrelin on glial activation in the hippocampus may involve the suppression of certain proinflammatory mediators, such as TNF-a, IL-1b, and COX-2. Moreover, in the present study, we found that Mmp3 expression was significantly increased in KA-injected mice as previously reported (Penkowa et al 2005), while ghrelin treatment suppressed Mmp3 levels through the activation of GHSR1a. Considering that MMP-3 plays a pivotal role in dopaminergic neurodegeneration in PD (Kim et al 2005 and ghrelin suppresses MPTP-induced Mmp3 expression ), ghrelin-mediated inhibition of Mmp3 expression in KA-induced neurotoxicity may provide another plausible therapeutic target to prevent progressive neurodegeneration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The underlying mechanisms of this inhibitory effect of ghrelin on glial activation in the hippocampus may involve the suppression of certain proinflammatory mediators, such as TNF-a, IL-1b, and COX-2. Moreover, in the present study, we found that Mmp3 expression was significantly increased in KA-injected mice as previously reported (Penkowa et al 2005), while ghrelin treatment suppressed Mmp3 levels through the activation of GHSR1a. Considering that MMP-3 plays a pivotal role in dopaminergic neurodegeneration in PD (Kim et al 2005 and ghrelin suppresses MPTP-induced Mmp3 expression ), ghrelin-mediated inhibition of Mmp3 expression in KA-induced neurotoxicity may provide another plausible therapeutic target to prevent progressive neurodegeneration.…”
Section: Discussionsupporting
confidence: 92%
“…It has been previously reported that Mmp3 is up-regulated in the hippocampus of KA-treated mice (Penkowa et al 2005), and Mmp3 is known to play an important role in dopaminergic neuronal cell death and neuroinflammation (Kim et al 2005. Therefore, we performed immunohistochemistry and RT-PCR to investigate the effect of ghrelin on KA-induced Mmp3 expression in the hippocampus.…”
Section: Ghrelin Attenuates Ka-induced Mmp3 Expressionmentioning
confidence: 97%
“…Previous studies suggest that inflammatory and apoptotic processes contribute to the later stages of the damage induced by brain injuries, and that these detrimentally affect neurologic outcome [5,21,22]. Therefore, we investigate the course alteration of proinflammatory cytokines mRNA on KA injection in the hippocampus.…”
Section: The Course Alteration Of Proinflammatory Cytokines Mrna On Kmentioning
confidence: 95%
“…glutamate), which are massively released as a consequence of energy depletion and which result in excitotoxic neuron death [2,3]. Recent studies have demonstrated that the KA-induced neuronal death is associated with the activation of microglia and astrocytes in the hippocampus, and that these processes are induced by enhanced reactive oxygen species (ROS) production and cytokine expressions [4,5]. The microglia also can be detected using the complement receptor type 3 (OX-42) IR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation